MENGENAL MUFASIR DAN KARYA TAFSIR - Pratama, Fingky Hendika; Elsya, Elsya (Jurnal Multidisipliner Kapalamada, 2024)
This article described the interpretation study carried out by the Mufassir in Indonesia. The term Mufassir is now important to revise in order to have that continuity among identity, tradition, and Al-Qur'an scientific study with their generations. The results showed that the practice of Qur'anic interpretation in Indonesia was spearheaded by Abdurrauf al-Singkil, Sheikh Nawawi al-Buntani, Mahmud Yunus, Ahmad Hasan Muhammad Hashbi Ash-Shiddiqy, HB Jassin, H. Bakri Syahid, Buya Hamka and Muhammad Quraish Shihab. The conclusion told that the style of interpretation in Indonesia contains three main dimensions, namely epistemology (source/method/criteria of Al-Qur'an knowledge), methodology (how to translate the dimensions of normativity of Al-Qur'an), and historical science. Therefore, the subjective nature of the Qur'an text turned into the objective nature of science text and then ethics (functioning the relationship between Al- Qur'an and social reality).